Words about Words about Words Theory, Criticism, and the Literary Text - Krieger, Murray (Johns Hopkins University Press, 2019)
Originally published in 1987. In Words about Words about Words, Murray Krieger advances his ongoing dialogue with the rich diversity of contemporary literary theory and elaborates on his own position as it grows out of an opposing relation to much of current criticism. Krieger examines the kinds of ideologies and ontologies smuggled into literary theory that purports to be anti-ideological and anti-ontological. He explores the extent to which critical fashions dictate the development of theory and the reasons why particular theories exclude certain kinds of literary works in favor of others. Under such circumstances, Krieger asks, What becomes of the critic's task of evaluation? Further, what is the relation of the idea of progress to criticism and the arts, and what is the effect of these notions on cultural and intellectual institutions? He seeks an alternative to the deterministic tendencies of the new historicism in viewing the relations of literature and literary criticism to society. Progressing from broad questions to more focused critical problems and close readings, Krieger reviews the aesthetic tradition as it has evolved from Kant. He engages in debate with deconstructionist critics about the role of symbol and allegory as descriptions of ways in which poems succeed or fail in constructing their verbal universe. And he argues that, for all its brilliance, deconstruction has not yet been able to fulfill the social or academic functions of the older, aesthetic-based disciplines that it set out to deconstruct.